Fungi as biotechnological allies: Exploring contributions of edible and medicinal mushrooms - Barua, Ramona Celeste (2024)
Edible and medicinal mushrooms possess excellent nutritional properties dueto their incredible versatility in growing on different substrates and producing extracellular enzymes with a wide range of specificity. These features makethem excellent candidates for various biotechnological applications. In this context, biotechnological applications using edible and medicinal mushrooms canfocus on the bioprocessing of agro-industrial wastes, an economical and environmentally friendly strategy. This review, based on recent original research andscientific reviews, highlights the versatility and potential of mushrooms in termsof sustainability and efficiency. We emphasized the biotechnological applicationsof edible and medicinal mushrooms and their enzymes including food production with high nutraceutical value by enhancing the quality and flavor of foodindustry products. Other biotechnological applications addressed in this reviewwere cosmeceutical and biomedical development using mushroom extracts withbioactive compounds; wood pulp pretreatment processes in the pulp and paperindustry; bioethanol production; and bioremediation for decontaminating soilsand polluted effluents. These applications explain how edible and medicinalmushrooms have gained significance in biotechnology over the years, openingnew avenues for innovation. The current tendency to study edible and medicinalmushrooms has gained the attention of researchers because these are still lessknown organisms becoming an attractive and natural source of novel bioactivecompounds that could be integrated into a circular model production.